Rare Genetic Risk in Progressive Supranuclear Palsy. (20th December 2022) - Chang, Timothy; Wang, Hui; Lee, Wan‐Ping; Kumar, Urvashi; Leung, Yuk Yee; Dickson, Dennis W.; Dalgard, Clifton L.; Wang, Li‐San; Schellenberg, Gerard D.; Geschwind, Daniel H.
Abstract: Background: Genetic risk in common variants have been identified for Progressive Supranuclear Palsy (PSP), but common variants only account for a portion of disease heritability. A proportion of the remaining disease heritability is likely contributed by rare variants identifiable via sequencing. Leveraging whole‐genome sequencing of 1719 PSP cases and 2940 controls from the Alzheimer's Disease Sequencing Project, we detected single nucleotide variants (SNVs), insertion/deletions (INDELs), and copy number variants (CNVs). Note that all samples are non‐Hispanic whites with identity by descent (IBD) >0.25, and no outlier is >6 standard deviation in the principal component analysis. We conducted association analysis for variants, genes and gene sets to identify rare genetic risk for PSP. Method: After quality control (variants and genotypes notated PASS by the calling algorithms), we detected 85, 228, 234 rare SNVs/INDELs and 163, 987 rare CNVs (minor allele frequency (MAF) < 1%). For rare SNVs/INDELs, the Sequence Kernel Association Test Optimized was performed to identify rare genetic PSP risk from protein truncating variants (PTV) and damaging missense variants (MAF<0.01%) in both protein coding genes and gene sets that were previously associated with PSP based on protein co‐expression networks. For rare CNVs, a permutation‐based association test implemented in Plink was performed to identify CNVs associated with PSP. Result: Combining protein truncating variants (PTV) and damaging missense variants, we identified one genome‐wide significant gene, FBXO38 (FDR = 0.0003, OR = 1.78). We also found enrichment of PTVs and damaging missense variants in genes comprising the C2 module, a neuronal module previously identified in post mortem PSP brain (FDR = 0.0016). For CNV analysis, there were 17 significant deletions and 2 significant duplications that were associated with PSP (Padjust < 0.05). The deletion (18:58488230‐58488489) in ALPK2, which has been identified as an Alzheimer's Disease risk gene, was the only CNV that conferred a higher‐risk for PSP. Particularly, one deletion (17:46009357‐46009595) was in linkage disequilibrium with MAPT H2 haplotype which has been associated various neurodegenerative diseases including PSP. Conclusion: We identified several new genes and a protein co‐expression network in which risk variants were associated with PSP. These genes and pathways provide potential candidate drug targets for future investigation.